Electric Competition and the Federal Energy Regulatory Commission - Santa, Donald (Maine Policy Review, 1994)
The pricing of electric power is not only an issue at the state level, it also gathers the attention of the Federal Energy Regulatory Commission. A major pricing issue now facing FERC involves electric transmission. This reflects increased competition in the electric generation business and is of particular concern in the wholesale electricity market, which is regulated by FERC. As FERC Commissioner Donald F. Santa makes clear in this article, access to transmission lines and the price to be paid for that access are extremely important issues to independent power producers. This article is based on Commissioner Santa's keynote speech to the PURE '94 Conference earlier this year.
Keywords: electric utilities; Federal Energy Regulatory Commission; FERC